Ensuring access to theses in the Arab speaking world – University of Jordan initiatives - Tbaishat, Dina (Digital library perspectives, 2018)
Purpose This paper aims to examine some of the digitization projects at the library of the University of Jordan. As the library acts as the deposit centre for theses from the Arab world universities, an effective management policy for deposit, management and access is required. The paper illustrates some of the existing workflows and considers the challenges and possible improvements. Design/methodology/approach Interviews (n = 8) with library staff in the Information Division provided details about the methods used for the collection and management of print and electronic theses in the University of Jordan, in addition to some digitization projects. In addition, very recent unpublished brochure was collected from one member of staff in the computer applications and databases section to learn about theses deposit statistics from various countries in the Arab world. A business process modelling technique (Riva) (Ould, 2005) using role activity diagram illustrated some of the existing workflows, the challenges and possible improvements. Findings Some Arab universities do not send theses on regular basis; some do not collaborate at all. Workflows vary according to the format of the thesis. The number of digitized print theses has reached 77,885 titles, out of total of 84,043, but it is a slow process. All newly submitted theses from Jordanian universities come in print and on a CD, but other external institutions may use different methods (CD only by mail, or direct uploading to the webpage provided by the University of Jordan). The current online system for uploading theses was last updated in 2017. Deposit rates through the system are very low. Access to theses is relatively limited; print theses can be accessed within the library premises. The online theses repository provides full text and all academic staff; students and researchers can access these from any workstation within the university campus. Only registered users may access theses databases (read only) outside the network. Resourcing for digitization is limited, and the digitization itself is currently outsourced although other processes are done in-house. Practical implications The paper encourages the use of a practical online theses’ repository to deposit theses from the higher education within the Arab world. Social implications Establishing theses repository and ensuring proper and smooth deposit process by Arab universities libraries, would enhance communication and collaboration amongst them. Originality/value The paper supports the theme of the primacy of global access to information for learning and scholarship. The paper adds value in the context of theses access amongst Arab universities. As the library acts as the deposit centre for theses from the Arab world universities, an effective management policy for deposit, management, access and preservation is required. The paper provides a set of recommendations that would contribute to raise the visibility of research produced by Arab higher education, through a single source of access to theses.